The handbook of China's financial system - Amstad, Marlene; Sun, Guofeng, 1972-; Xiong, Wei, 1971- (Princeton University Press, 2020)
"The Chinese economy is now easily one of the most important and closely scrutinized economies in the world. Relatively minuscule changes in predictions of how the Chinese economy will perform can drive up or down stocks and the price of oil and other commodities. At the heart of how the Chinese economy works is its financial system-but the Chinese financial system is vastly different than most people in the West can understand. How do house prices work, for example, in a country where the very concept of property ownership is significantly different than our own? This edited volume will serve as a standard reference guide to China's financial system. With eighteen chapters, the handbook features overviews on the banking sector-the core of China's financial system and the key channel for implementing China's monetary policy-China's ongoing reforms, and the quickly growing bond and money markets, among other topics. Each chapter is written by a leading expert in the field, and as a whole the list of contributors represents an impressive mix of leading scholars and high-level policy officials, some with first-hand knowledge of setting and carrying out Chinese financial policy. The handbook will serve as the first real authoritative volume of literature in the field, and will shed extensive new light on the links between China's financial system and the real economy"--